Analysis of seismic and mareographic series for the characterization of calving events in the Wolstenholme fjord, Greenland - Sonet, Federico (Alma Mater Studiorum - Università di Bologna, 2025)
Ice sheets lose mass through several processes: one is the calving of ice at the end of outlet glaciers. This process releases seismic energy and generates large tsunami waves as the ice collapses into the water and eventually capsizes. The great variability of the phenomenon and the complex dynamics involved make its study challenging. Moreover, observations are still not well understood and remain difficult to interpret. In this work, we aim to take a step forward in understanding the phenomenon by attempting to localize events associated with calving through the joint analysis of mareographic and seismic data. Through these indirect but continuous observations of the phenomenon, we will focus on four events that occurred between August 2021 and September 2022 in Wolstenholme Fjord, Greenland. After detecting possible events using mareographic observations, we will localize them with two different methods using seismic data. Finally, we will attempt to validate the results with a numerical simulation of tsunami propagation in the fjord.